ANALISIS PERSEPSI DAN MOTIVASI PETANI TERHADAP MANFAAT SUMBERDAYA HUTAN LINDUNG PULAU TARAKAN - Sutrisno, Adi (SOROT, 2012)
The research aims is to find the main causes of disharmony between behaviorof users community and the management objectives of Protection Forest Resourceof Tarakan Island that reviewed based on the perceptions and motivations. Based onthe research results: First, the level of perception of the users farmer of ProtectionForest Resource of Tarakan Island in the direct use included in the medium category,but for the functional benefits and the optional benefits included in the low category.While, the level perception of the existential benefits included in medium categoryand other benefits include high category. Second, the level of economic andenvironmental motivations of users farmer in utilization of Protection Forest Resourceof Tarakan Island is low, but the level of social motivation toward Protection ForestResource of Tarakan Island is high. Third, the low level of users’ farmer perception offunctional and optional benefits, low levels of economic and environment motivation,and the high social motivation of the users’ farmer in utilization Protection ForestResource of Tarakan Island become the main causes of disharmony betweenbehavior of users farmer and the management objectives of Protection ForestResource of Tarakan Island.